Scenario thinking : practical approaches to the future - Wright, George. (Palgrave Macmillan, 2011)
"Presents new methods in scenario thinking, based on a mix of high-level research and top-level consultancy experience. The authors describe the logical bases of a range of scenario methods and provide detailed 'road maps' on how to implement them - together with practical examples of their application"--